The Ghosts of Tupelo Landing - Turnage, Sheila (New York, New York : Kathy Dawson Books, an imprint of Penguin Group (USA Inc., 2014)
"When Miss Lana accidentally buys a haunted inn at the Tupelo Landing town auction, Desperado Detectives--aka Mo LoBeau and her best friend Dale--opens up a paranormal division to solve the ghost's identity before the town's big 250th anniversary bash"--
Keywords: Hotels -- Juvenile fiction; Haunted places -- Juvenile fiction; Ghost stories; Community life -- Juvenile fiction -- North Carolina; Identity (Psychology) -- Juvenile fiction; Foundlings -- Juvenile fiction; Detective and mystery stories; Mystery and detective stories; Hotels -- Fiction; Haunted places -- Fiction; Ghosts -- Fiction; Community life -- Fiction -- North Carolina; Identity -- Fiction; Foundlings -- Fiction; North Carolina -- Juvenile fiction; North Carolina -- Fiction